2020
DOI: 10.3389/fnagi.2020.00158
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Hippocampal Memory Function in Older Adults Through Real-World Exploration

Abstract: Age-related structural and functional changes in the hippocampus can have a severe impact on hippocampal-dependent memory performance. Here, we tested the hypothesis that a real-world spatial exploration and learning intervention would improve hippocampal-dependent memory performance in healthy older adults. We developed a scavenger hunt task that participants performed over the course of a 4-week behavioral intervention period. Following this intervention, participants' lure discrimination index (LDI) on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Even modest amounts of gameplay (e.g., 30 min/day over 2-4 weeks) improved performance on a hippocampal dependent memory task while not affecting a simpler recognition memory task that is far less reliant upon the hippocampus. We should note that while long-term follow-up data were not available here, our prior studies have shown little decline when tested 2-8 weeks after the intervention (Clemenson and Stark, 2015;Clemenson et al, 2020;Kolarik et al, 2020), suggesting the effects are not terribly short-lived.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Even modest amounts of gameplay (e.g., 30 min/day over 2-4 weeks) improved performance on a hippocampal dependent memory task while not affecting a simpler recognition memory task that is far less reliant upon the hippocampus. We should note that while long-term follow-up data were not available here, our prior studies have shown little decline when tested 2-8 weeks after the intervention (Clemenson and Stark, 2015;Clemenson et al, 2020;Kolarik et al, 2020), suggesting the effects are not terribly short-lived.…”
Section: Discussionmentioning
confidence: 79%
“…There, what was not enriching to young adults (Free Building) showed a modest effect in middle-aged participants (who were playing a novel immersive 3D game, albeit in a more spartan mode; middle bar), paralleling the improvement in Angry Birds found in older adults. Finally, we have investigated this effect outside the realm of computerized video games to a real-world enrichment paradigm in older adults (Kolarik et al, 2020). Here, adults performed a scavenger-hunt style game in a local park, learning the locations associated with 20 cues over the course of a week before shifting to another park in a 1-month intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In several prior interventional studies using young (Clemenson and Stark, 2015 ; Clemenson et al, 2019 ), middle-aged (Stark et al, 2021 ), and older adults (Clemenson and Stark, 2017 ; Kolarik et al, 2020 ; Wais et al, 2021 ), the MST’s LDI metric has shown no clear sign of practice effects. Yet, at least in the version used by CogState, at least two studies have shown not only practice effects (Papp et al, 2020 ) but the potential predictive power of such effects in diagnosing clinical cognitive decline (Jutten et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results linking behavioral pattern separation, trait-like appraisals of daily life stressors, and subjective state reactivity to a robust laboratory stressor suggest a potential behavioral target for research on preventive behavioral interventions that enhance psychological resilience by modifying appraisals of stressors, such as cognitive and mindfulness-based therapies ( Beck, 1976 ; Teasdale et al, 2000 ). Because pattern separation behavior is a malleable process sensitive to behavioral interventions ( Clemenson et al, 2020 ; Clemenson and Stark, 2015 ; Kolarik et al, 2020 ), an intriguing direction for future research is testing whether interventions that modify stress appraisals elicit corresponding improvements in behavioral pattern separation (or vice versa).…”
Section: Discussionmentioning
confidence: 99%